2019
DOI: 10.1016/j.jstrokecerebrovasdis.2018.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Stride Management Assist Gait Training for Poststroke Hemiplegia: A Single Center, Open-Label, Randomized Controlled Trial

Abstract: Background: Poststroke gait disorders negatively impact activities of daily living. Rehabilitation for stroke patients is aimed at improving their walking ability, balance, and quality of life. Robot-assisted gait training (RAGT) is associated with an increased number of task-specific exercises, which may benefit poststroke motor learning. We investigated the effects of RAGT using Stride Management Assist (SMA, which increases walk ratio by inducing hip-joint flexion and extension) in subacute stroke patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 36 publications
2
31
4
1
Order By: Relevance
“…The RAGT induced the expansion of hip joint angles on the affected side. These results are consistent with the results of previous studies that have reported the increase of the limb symmetry after the intervention with the HWA [9]. These previous studies recruited individuals with the first stroke, who mostly have only one leg paralyzed.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The RAGT induced the expansion of hip joint angles on the affected side. These results are consistent with the results of previous studies that have reported the increase of the limb symmetry after the intervention with the HWA [9]. These previous studies recruited individuals with the first stroke, who mostly have only one leg paralyzed.…”
Section: Discussionsupporting
confidence: 92%
“…Despite the significant changes in gait kinematics and kinetics, there was no significant change in gait speed. This result is inconsistent with some previous studies which have reported a significant change in maximum walking speed of stroke individuals after 10-day intervention [9]. This inconsistency may be due to the slow treadmill speed settings because the HWA could not produce the assistive torques to the gait with a high pitch.…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…Although the HWA has previously been used as a means of gait training for individuals with stroke [12,13], there is no study, to the best of our knowledge, that has used the HWA to improve the gait of amputees, i.e., the safety and feasibility of the HWA are unknown in TF amputees who have problems with stump shortness, socket-thigh cuff interference, and high susceptibility to skin problems. In this study, we investigated the safety, feasibility, and efficacy of gait training using the HWA in two amputees.…”
Section: Introductionmentioning
confidence: 99%